2023
DOI: 10.3390/cancers15082312
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FLT3 Mutation in Acute Myeloid Leukemia: Current Strategies and Future Directions

Abstract: FLT3 mutations are present in 30% of newly diagnosed patients with acute myeloid leukemia. Two broad categories of FLT3 mutations are ITD and TKD, with the former having substantial clinical significance. Patients with FLT3-ITD mutation present with a higher disease burden and have inferior overall survival, due to high relapse rates after achieving remission. The development of targeted therapies with FLT3 inhibitors over the past decade has substantially improved clinical outcomes. Currently, two FLT3 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
(100 reference statements)
0
12
0
Order By: Relevance
“…131 In recent years, targeting FLT3 has been an integral component of treatment regimens for FLT3-ITD/ TKD-mutated AML patients, leading to significantly extended survival rates. 132 Despite the clinical availability of FLT3 inhibitors, their impact on survival outcomes remains modest. 133 In 2023, Yashar et al reported that combining an LSD1 inhibitor GSK-2879552 and an FLT3 inhibitor Quizartinib exhibited a synergistic effect in inducing cell death in FLT3 mutant AML (Table 2).…”
Section: Combination Of Lsd1 Inhibitor and Flt3mentioning
confidence: 99%
See 1 more Smart Citation
“…131 In recent years, targeting FLT3 has been an integral component of treatment regimens for FLT3-ITD/ TKD-mutated AML patients, leading to significantly extended survival rates. 132 Despite the clinical availability of FLT3 inhibitors, their impact on survival outcomes remains modest. 133 In 2023, Yashar et al reported that combining an LSD1 inhibitor GSK-2879552 and an FLT3 inhibitor Quizartinib exhibited a synergistic effect in inducing cell death in FLT3 mutant AML (Table 2).…”
Section: Combination Of Lsd1 Inhibitor and Flt3mentioning
confidence: 99%
“…FLT3 mutations are common genetic alterations detected in AML, with approximately 30% of newly diagnosed patients . In recent years, targeting FLT3 has been an integral component of treatment regimens for FLT3-ITD/TKD-mutated AML patients, leading to significantly extended survival rates . Despite the clinical availability of FLT3 inhibitors, their impact on survival outcomes remains modest …”
Section: Combination Of Lsd1 Inhibitors and Other Target-based Inhibi...mentioning
confidence: 99%
“…FMS-like tyrosine kinase-3 (FLT3) is one of many human tyrosine kinases [45,46]. Tyrosine kinases belong to a group of enzymes that catalyze the phosphorylation of select tyrosine residues in target proteins using ATP.…”
Section: Flt3mentioning
confidence: 99%
“…FLT3-ITD mutated AML displays heterogeneity, which can be attributed to variations in ITD length, insertion site, mutant-to-wild type allele ratio (AR), overall karyotype, and co-occurring mutations, particularly NPM1 [45]. Regardless of other factors, the presence of FLT3-ITD mutation alone in patients newly diagnosed is associated with unfavorable outcomes in terms of relapse-free (RFS) and overall survival (OS) compared to patients with wild-type FLT3 (WT-FLT3) [45,49,53]. It should be pointed out that until recently, the impact of an FLT3 mutation on the prognosis of patients struggling with AML was considered to be dependent on the ratio of mutated to wild-type allele [54].…”
Section: Flt3 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation